Step
*
1
1
2
1
1
of Lemma
arctan-poly-approx-1
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. ∀x:ℝ. -(x^2) ≠ r1
3. x : {x:ℝ| r0 ≤ x}
4. k : ℕ
5. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
6. i : ℤ
7. 0 ≤ i
8. i ≤ k
⊢ (if (i rem 2 =z 0) then x^(2 * i) + 1 else -(x^(2 * i) + 1) fi )/(2 * i) + 1 = r0_∫-x -(x^2)^i dx
BY
{ (Assert r0_∫-x -(x^2)^i dx = r0_∫-x r(-1)^i * x^2 * i dx BY
(BLemma `integral_functionality` THEN Auto)) }
1
.....aux.....
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. ∀x:ℝ. -(x^2) ≠ r1
3. x : {x:ℝ| r0 ≤ x}
4. k : ℕ
5. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
6. i : ℤ
7. 0 ≤ i
8. i ≤ k
9. x1 : ℝ
10. rmin(r0;x) ≤ x1
11. x1 ≤ rmax(r0;x)
⊢ -(x1^2)^i = (r(-1)^i * x1^2 * i)
2
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. ∀x:ℝ. -(x^2) ≠ r1
3. x : {x:ℝ| r0 ≤ x}
4. k : ℕ
5. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
6. i : ℤ
7. 0 ≤ i
8. i ≤ k
9. r0_∫-x -(x^2)^i dx = r0_∫-x r(-1)^i * x^2 * i dx
⊢ (if (i rem 2 =z 0) then x^(2 * i) + 1 else -(x^(2 * i) + 1) fi )/(2 * i) + 1 = r0_∫-x -(x^2)^i dx
Latex:
Latex:
1. \mforall{}x:\mBbbR{}. (r0 < (r1 + x\^{}2))
2. \mforall{}x:\mBbbR{}. -(x\^{}2) \mneq{} r1
3. x : \{x:\mBbbR{}| r0 \mleq{} x\}
4. k : \mBbbN{}
5. r0\_\mint{}\msupminus{}x (r1/r1 + x\^{}2) - \mSigma{}\{-(x\^{}2)\^{}i | 0\mleq{}i\mleq{}k\} dx = (arctangent(x) - r0\_\mint{}\msupminus{}x \mSigma{}\{-(x\^{}2)\^{}i | 0\mleq{}i\mleq{}k\} dx)
6. i : \mBbbZ{}
7. 0 \mleq{} i
8. i \mleq{} k
\mvdash{} (if (i rem 2 =\msubz{} 0) then x\^{}(2 * i) + 1 else -(x\^{}(2 * i) + 1) fi )/(2 * i) + 1 = r0\_\mint{}\msupminus{}x -(x\^{}2)\^{}i dx
By
Latex:
(Assert r0\_\mint{}\msupminus{}x -(x\^{}2)\^{}i dx = r0\_\mint{}\msupminus{}x r(-1)\^{}i * x\^{}2 * i dx BY
(BLemma `integral\_functionality` THEN Auto))
Home
Index